The Social Accountability Paradox in the Regional Democratic Budget Policy Making - Hastjarjo, Sri; Wahyunengseh, Rutiana Dwi (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2015)
Social accountability has been believed as an approach to overcome the deficit of the formal accountability (both horizontal and vertical accountability). Social accountability is percieved as a public accountability which is initiated by and aimed for the society. Several studies found the effectiveness of social accountability in encouraging a more transparent government and a wider public involvement. Those studies identified variables which contribute to the social accountability, i.e. the degree of government openness; the density of community organizations and their advocation capability; social, political, and cultural environment; and the public information accessibility. Data for this paper is collected through in-depth interviews and focused group discussion with the major players in the budget policy making process, including local government officers, members of local house of representatives (DPRD), and activists of the local community groups in the Regency of Karanganyar. This paper argues that despite its effectiveness, social accountability also produce some counterproductive excesses. The term social accountability paradox is used in this paper to represent the abuse of social accountability and it risks. This paper aims to identify the practices of social accountability abuse in the local budget policymaking process, with the case of the Regency of Karanganyar. Based on the study, there are some requirement to be fulfilled In order to increase the social accountability of the public budget policy making process, i.e. (1) revision of regulations to encourage a more transparency in the budget public information; (2) the development of community-based monitoring and dialogues forums; and (3) the increasing of the capability of community groups in conducting social accountability audit.